Komposisi Tari Manuk Jeletik Di Sanggar Gdeng Kedaton, Puri Dalem, Desa Lendang Nangka, Kecamatan Masbagik, Kabupaten Lombok Timur-NTB. - Farida, Hilda; Suci, Baiq Widia Komala (Jurnal Ilmiah Wahana Pendidikan, 2023)
The Manuk Jeletik dance is a new dance creation in the Gdeng studio, Kedaton Puri Dalem, Lendang Nangka Village, Masbagik Subdistrict, East Lombok Regency, West Nusa Tenggara. This study aims to determine the composition of the Manuk Jeletik dance in the Gdeng Kdaton studio, Puri Dalem, Lendang Jackfruit. other. The results of this study indicate that there are seven compositions of the Manuk Jeletik dance, namely: 1.)theme, 2).movement, 3).floor pattern, 4).music/accompaniment, 5).fashion/costume, 6). make-up, 7).and lighting.